Ge‐Mediated Modification in Ta3N5 Photoelectrodes with Enhanced Charge Transport for Solar Water Splitting. Issue 49 (14th October 2014) - Feng, Jianyong; Cao, Dapeng; Wang, Zhiqiang; Luo, Wenjun; Wang, Jiajia; Li, Zhaosheng; Zou, Zhigang
Abstract Ta3N5 is a promising photoanode candidate for photoelectrochemical water splitting, with a band gap of about 2.1 eV and a theoretical solar‐to‐hydrogen efficiency as high as 15.9 % under AM 1.5 G 100 mW cm−2 irradiation. However, the presently achieved highest photocurrent (ca. 7.5 mA cm−2) on Ta3N5 photoelectrodes under AM 1.5 G 100 mW cm−2 is far from the theoretical maximum (ca. 12.9 mA cm−2), which is possibly due to serious bulk recombination (poor bulk charge transport and charge separation) in Ta3N5 photoelectrodes. In this study, we show that volatilization of intentionally added Ge (5 %) during the synthesis of Ta3N5 promotes the electron transport and thereby improves the charge‐separation efficiency in bulk Ta3N5 photoanode, which affords a 320 % increase of the highest photocurrent comparing with that of pure Ta3N5 photoanode under AM 1.5 G 100 mW cm−2 simulated sunlight.